Returns, metamorphoses and otherness: from Kafka to Murakami, between text and discourse - Terracciano, Bianca (E|C, 2024)
Haruki Murakami, one of the most influential contemporary Japanese writers, weaves numerous intertextual references to Franz Kafka into his works, crafting narratives that explore the tension between the individual and the system, the search for meaning, and the absurd. Winner of the sixth annual Franz Kafka Society Prize in 2006, Murakami shares with the Bohemian author a rhizomatic narrative approach, delving into becoming and existence. Through a semiotic perspective, deep similarities between the two authors emerge: Murakami resemanticizes Kafka’s style, adapting narrative frameworks he considers effective. This analysis examines the relationship between text and discourse through implicit and explicit references to Kafka in Murakami’s works, seen as the result of cultural translation, reassembling possible worlds. This intricate network goes beyond homage, exploring shared narrative invariants such as actantial roles, thematic figures, and frames that shape their respective universes of meaning.